# Difference between revisions of "2011 AMC 12A Problems/Problem 23"

## Problem

Let $f(z)= \frac{z+a}{z+b}$ and $g(z)=f(f(z))$, where $a$ and $b$ are complex numbers. Suppose that $\left| a \right| = 1$ and $g(g(z))=z$ for all $z$ for which $g(g(z))$ is defined. What is the difference between the largest and smallest possible values of $\left| b \right|$? $\textbf{(A)}\ 0 \qquad \textbf{(B)}\ \sqrt{2}-1 \qquad \textbf{(C)}\ \sqrt{3}-1 \qquad \textbf{(D)}\ 1 \qquad \textbf{(E)}\ 2$

## Solution

Answer: (C) $\sqrt{3} - 1$

Lemma) if $f(z) = \frac{z + a}{z + b}$, then $f(f(f(f(\frac{-a(1+b)}{a+1})))) = \frac{a ( 1 + b)}{ a+b^2}$ $f(f(f(f(\frac{-a(1+b)}{a+1})))) = f(f(f(-a))) = f(f(0)) = f(\frac{a}{b}) = \frac{a + ab}{a + b^2}$

The tedious algebra is left to the reader. (it is not bad at all)

Well, let us consider the cases where each of those step is definite ( $f(-b)$ is never evaluate).

So, we have $\frac{-a(1+b)}{a+1} \neq - b$, $-a - ab \neq - ab - b$ $a \neq b$ --- (exception -> case 2) $-a \neq -b$ --- (exception -> case 3) $0 \neq -b$ --- (exception -> case 4) $\frac{a}{b} \neq -b$ $a \neq -b ^2$ --- (exception -> case 5)

If it is not any of the above 5 cases, then $\frac{-a(1+b)}{a+1} = \frac{a + ab}{a + b^2}$

if $a(1+b) \neq 0$ (--- exception -> case 6), then $-(a+b^2) = a+1$, $b^2 = -2a - 1$, $1 \le |b^2| \le 3$

Hence, it is possible maximum of $|b| = \sqrt{3}$ and minimum is 1.

2 possible combination of $(a,b)$ are $(1, 3i)$ and $(-1, 1)$. Verification is left upto the reader. Right now, (C) is the most possible answer out of those 5.

Case 2) $a = b$, then $|b| = 1$

Case 3) $|b|$ = 1, which is in the range.

Case 5) $b^2 = -a$, hence $|b| = 1$

Case 6) Since $a \neq 0$, $(1+b) = 0$, $|b| = 1$

Case 4) $b = 0$, this is quite an annoying special case. In this case, $f(z) = \frac{z+a}{z}$, $f(0)$ is not define.

In this case, $f(f(f(f(\frac{a}{a-1})))) = f(f(f(a)))= f(f(2)) = f( \frac{2+a}{2}) = \frac{2+3a}{2+a}$ and $f(f(f(f(\frac{a}{a-2})))) = f(f(f(2a)))= f(f(\frac{3}{2})) = f( \frac{3+2a}{3}) = \frac{3+5a}{3+2a}$

Hence, $(2+a)a = (a-1)(2+3a)$ and $(a)(3+2a) = (a-2)(3+5a)$. Once, you work out this system, you will get no solution with $|a| = 1$.